The Influence of Career Development, Competence, Work Motivation, Job Satisfaction, Against the Performance of Health Service Employees in Bintan Regency - Putri Rahmawati; Verlina Y Kawangung; Didi Kurniadi; Faisal Husni (IAIC International Conference Series, 2021)
This study uses a causal model survey method using path analysis techniques. This study aims to confirm the theoretical model with empirical data, the study population is employees in the Bintan Regency Health Office, which consists of civil servants and honorary employees with samples of 89 employees. Data collecting technical using variable measurements by questionnaire instruments, this instrument was developed based on theoretical studies. Data analysis uses descriptive statistics and statistical analysis. Statistical tests are used to test the significance of path coefficients using Partial Least Square (PLS) which is a Multivariate Analysis in the second generation using structural equation modeling (SEM). PLS can be used for a small number of samples and does not require the assumption that data distribution must be normal or not. The results of the analysis found that relationships between variables formulated in the formulation of the problem as many as 6 pieces obtained significant.